Collapsing Focal Segmental Glomerulosclerosis in Siblings With Compound Heterozygous Variants in NUP93 Expand the Spectrum of Kidney Phenotypes Associated With Nucleoporin Gene Mutations - Rachel K. Cason; Anna Williams; Megan Chryst-Stangl; Guanghong Wu; Kinsie Huggins; Kaye E. Brathwaite; Brandon M. Lane; Larry A. Greenbaum; Vivette D. D’Agati; Rasheed A. Gbadegesin (Frontiers in Pediatrics, 2022)
BackgroundFocal segmental glomerulosclerosis (FSGS) is a major cause of end stage kidney disease, with the collapsing form having the worst prognosis. Study of families with hereditary FSGS has provided insight into disease mechanisms.MethodsIn this report, we describe a sibling pair with NUP93 mutations and collapsing FSGS (cFSGS). For each brother, we performed next generation sequencing and segregation analysis by direct sequencing. To determine if the variants found in the index family are a common cause of cFSGS, we screened 7 patients with cFSGS, gleaned from our cohort of 200 patients with FSGS, for variants in NUP93 as well as for APOL1 high-risk genotypes.ResultsWe identified segregating compound heterozygous NUP93 variants (1) c.1772G > T p.G591V, 2) c.2084T > C p.L695S) in the two brothers. We did not find any pathogenic variants in the seven patients with cFSGS from our cohort, and as expected five of these seven patients carried the APOL1 high-risk genotype.ConclusionTo the best of our knowledge, this is the first report of cFSGS in patients with NUP93 mutations, based on this report, mutations in NUP93 and other nucleoporin genes should be considered when evaluating a child with familial cFSGS. Determining the mechanisms by which these variants cause cFSGS may provide insight into the pathogenesis of the more common primary and virus-mediated forms of cFSGS.